The influence of the kinds of nitrogen và the light in Ganoderma lucidum submerged culture - Nguyen, Phan Khanh Hoa; Pham, Thi Cam Hoa; Le, Thi Thuy Tien (JST: Engineering And Technology For Sustainable Development, 2023)
The survey was conducted to select the nitrogen sources and suitable light conditions during Viet Nam G. lucidum submerged culture (strain DL). The results showed that organic nitrogen is more suitable than inorganic nitrogen for the growth and synthesis of fungal polysaccharides. The amounts of IPS and EPS in this strain was highest when combined 7.5 g/l yeast and 2.5 g/l peptone. The light affected on the size, shape and the color of the DL cells in submerged culture. Under optimum conditions for nitrogen and light sources, the biomass, IPS and EPS content of DL strain were 13.897 ± 0.274 g DW/l, 15.33 ± 0.97 mg/100mg DW and 2349.76 ± 46.94 mg/l, respectively.